Dua Tangan Allah Merangkul Semesta: Panentheisme dan Theenpanisme - Joas Adiprasetya (Asosiasi Teolog Indonesia, 2017)
This article proposes a Trinitarian imagination that demonstrates the embrace of the whole universe by the Son and the Holy Spirit, the two hands of God, through the creation and perfection of the universe. Both divine acts take place in the incarnation of the Son and the inhabitation of the Holy Spirit. The Trinitarian perichoretic principle also applies to the relationship between God and creation in such a way that, not only is the whole universe in the Son (panentheism), but so too the Holy Spirit permeates the whole universe (theenpanism). As a result, Christian theology offers a comforting pastoral message, namely, that the universe is never entirely separable from the loving communion of the Triune God.